Commercially available chemicals as immunizing haptens for the development of a polyclonal antibody recognizing carbendazim and other benzimidazole-type fungicides. (January 2015) - Zikos, Christos; Evangelou, Alexandra; Karachaliou, Chrysoula-Evangelia; Gourma, Georgia; Blouchos, Petros; Moschopoulou, Georgia; Yialouris, Constantinos; Griffiths, John; Johnson, Graham; Petrou, Panagiota; Kakabakos, Sotirios; Kintzios, Spyridon; et al.
Abstract: Carbendazim is a fungicide widely used for controlling fungi affecting fruits, vegetables, field crops etc. Determination of carbendazim in water, soil and various crops is frequently required to assure compliance with national/European regulations. A polyclonal antibody recognizing carbendazim was developed by using commercially available 2-(2-aminoethyl) benzimidazole, 2-benzimidazole propionic acid and 2-mercaptobenzimidazole as immunizing haptens; each of the above derivatives was directly conjugated to the carrier protein keyhole limpet hemocyanin and a mixture of the conjugates was administered to New Zealand white rabbits. Immunochemical functionality of the antisera and the corresponding isolated antibody (whole IgG fraction) was evaluated through titer and displacement curves in an in-house developed ELISA, which employed a 2-mercaptobenzimidazole – functionalized lysine-dendrimer as the immobilized hapten. As shown with ELISA-displacement curves, the above antibody could recognize carbendazim as well as other benzimidazole-type fungicides, i.e. benomyl and thiabendazole, and also intact benzimidazole, while it did not cross-react with the structurally different pesticides carbaryl and imazalil. Considering the rather simple approach which has led to its development and its highly promising immunochemical profile, the new antibody may be exploited in immunoanalytical systems for detecting benzimidazole-type pesticides e.g. in samples of environmental interest. The above antibody is being currently tested as a biorecognition element in the novel FOODSCAN cell biosensor platform for pesticide residue detection based on the Bioelectric Recognition Assay technology.